Legal Opportunity Structure and Legal Battles Over Sex Education and LGBTQ Students in Brazil and Colombia - Ana de Mello Cortes; Juliana Jaramillo (Revista Direito GV)
Abstract Brazil and Colombia are outstanding cases of rights recognition through courts. However, when it comes to comprehensive sex education (CSE), the legal battles in these countries have experienced notably different moments. Drawing on judicial cases from the Brazilian Federal Supreme Court and the Colombian Constitutional Court, we identify the actors involved in the legal battles over CSE and show how the legal opportunity structure (i.e., the configuration of power, the access to the courts, the systems of alliance and conflicts, and the availability of legal frames) shaped the course and outcomes of the legal mobilization that took place in these countries in different ways. For this, we work with document analysis of court case files and consider a sample established in February 2023 containing 9 cases from Brazil and 24 cases from Colombia. We argue that (i) the Colombian court is much more open to civil society than the Brazilian court, resulting in a broader and more diversified use of litigation, and that (ii) the different configuration of political power has led the Brazilian mobilization to assume a feature of resistance to conservative attacks on CSE, while in Colombia, litigation has become a tool for expanding the right to sex education and protecting LGBTQ students.